Do investments in water management research pay?: an analysis of water management research in India - Kuppannan, Palanisami; Kakumanu, Krishna Reddy; Kumar, D.S.; Challamuthu, S.; Chandrasekaran, B.; Ranganathan, C.R.; Giordano, Mark (IWA Publishing, 2012)
Even though there has been increasing development of water management technologies over the years, the adoption rate by the farmers is comparatively small ranging from only 15-20%. Hence it is timely to look at the return to water management research investment to fine tune investment in future research. A detailed study was done using the data from Tamil Nadu State, India. The successful technologies yielded a moderate return ranging from 11?20%. With higher adoption levels of the water management technologies, the rate of return will be higher. Strategies to boost technology transfer and upkeep should be given importance in water management programmes.